Investigation of the limits of high-definition muography for observation of Mt Sakurajima. (10th December 2018) - Oláh, László; Tanaka, Hiroyuki K. M.; Hamar, Gergő; Varga, Dezső
Abstract : A multi-wire proportional chamber-based muo- graphy observatory is under development for the monitoring of the internal structure of Mt Sakurajima in Kyushu, Japan. We investigated the limits of large-scale and high-definition muography. We adjusted the parameters of a modified Gaisser model and found that the spectral index of γ = − 2.64 and normalization factor of C = 0.66 reproduce more accurately the measured fluxes than the original parameters at large thickness. A thickness and zenith angle-dependent correction is suggested to the measured muon flux due to the energy cut which is introduced to suppress the background particles. The multiple scattering of muons was simulated across the standard rock and sea-level atmosphere up to the distance of 5 km. We found that multiple scattering decreases from 10 mrad to 4 mrad across the rock due to the decrease in the steepness of muon spectra. The multiple scattering falls down to about 2 mrad after the object in the atmosphere due to the increase in observed arrival zenith angles. The 2 m 2 sized multi-wire proportional chamber-based Muographic Observation System (MMOS) was operating between February and June 2018. Three tracking systems operated reliably with tracking efficiencies of above 95%. The muon flux has been measured correctly down to 10 −3 m −2 sr −1 s −1 . The average density map of Mt Sakurajima has been measured with angular resolution of 12 mrad × 12 mrad (spatial resolution of 34 m × 34 m from the distance of 2.8 km). The average density values were found between 1.4 and 2 g cm −3, except at the crater regions where lower densities were observed. This article is part of the Theo Murphy meeting issue 'Cosmic-ray muography'.